ISOLASI DAN PEMEKATAN ENZIM SELULASE Trichoderma sp. LBKURCC28 MENGGUNAKAN METODE PENGGARAMAN (NH 4 ) 2SO 4 80% SERTA PENENTUAN AKTIVITAS DAN AKTIVITAS SPESIFIK ENZIM - Febry Kurniawan; Titania T. Nugroho; Andi Dahliaty (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Cellulase enzyme activity can be increased by concentrating the enzyme using saturated ammonium sulfate ((NH4) 2SO4) 80%. Precipitated enzyme was redissolved by the addition of acetate buffer solution pH 5.5 to 1/70 times its original volume. Cellulase enzyme activity was determined using substrates CMC and avicel. The test results showed that the activity of concentrated CMCase increased 75 times and avicelase enzyme activity increased 9 times. Activity and specific activity concentrated CMCasewas 0,4060±0,0845 U/ml and 0,7306±0,1526 U/mg respectively, while activity and specific activity of concentrated avicelase were 0,0129±0,0182 U/ml and 0,0232±0,0328 U/mg respectively.